Effect of acute high-intensity interval exercise on a mouse model of doxorubicin-induced cardiotoxicity: a pilot study - Elise P. Legault; Paula A. B. Ribeiro; Daniil R. Petrenyov; Gergana O. Drumeva; Charles Leduc; Sharmila Khullar; Jean N. DaSilva; Alain Steve Comtois; François B. Tournoux (BMC, 2024)
Abstract Background It is unknown whether high-intensity interval exercise (HIIE) may potentiate or attenuate the cardiotoxic effect of chemotherapy agents such as doxorubicin (DOX) when performed shortly after treatment. The study aimed to investigate the effect of acute HIIE on cardiac function and structure performed either 1, 2 or 3 days after DOX injection in an animal model. Methods Female C57bl/6 mice (n = 28), 70 days old, received a bolus 20 mg/kg intravenous tail vein DOX injection. Three exercise groups performed 1 HIIE session (16 sets of 1 min at 85-90% of peak running speed) at 1 (n = 7), 2 (n = 7), and 3 days (n = 8) following the DOX injection. A sedentary (SED) group of mice (n = 6) did not exercise. Animals underwent echocardiography under light anesthesia (isoflurane 0.5-1%) before and 7 days after the DOX injection. Animals were sacrificed on day 9 and hearts were collected for morphometric and histological analysis. Results Animals exercising on day 3 had the smallest pre-post reduction in left ventricular fractional shortening (LVFS) (MΔ= -1.7 ± 3.3; p = 0.406) and the SED group had the largest reduction (MΔ=-6.8 ± 7.5; p = 0.009). After reclassification of animals according to their exercise compliance (performing > 8/16 of high-intensity bouts), LVFS in compliant mice was unchanged over time (LVFS MΔ= -1.3 ± 5.6; p = 0.396) while non-compliant animals had a LVFS reduction similar to sedentary animals. There were no significant differences in myocardial histology between groups. Conclusions In this pilot murine study, one single HIIE session did not exacerbate acute doxorubicin-induced cardiotoxicity. The timing of the HIIE session following DOX injection and the level of compliance to exercise could influence the negative impact of DOX on cardiac function.